Improving Learning Outcomes of Hal Nun Sukun and Tanwin Tajweed Subjects Through Talkhis and Taqshir Methods in Class VII D MTs "Al-Islam" Joresan - Puput Laila Hanum; Imam Rohani (Tarbawi: Journal of Islamic Education, 2023)
This study aims to determine how effective the Talkhis and Taqshir methods are in improving the learning outcomes of class VII D MTs "Al-Islam" Joresan in the subject of Tajwid Hal Nun Sukun and Tanwin. The research subjects were class VII D MTs "Al-Islam" Joresan, totaling 30 students, consisting of 15 boys and 15 girls. This research is a classroom action research (CAR) which consists of two cycles with the design of each cycle consisting of four stages, namely the first stage is planning, the second stage is acting (implementing), observing (observing) and the fourth stage is reflecting ( reflect). Research data is obtained during action research until the final assessment of the action. The results showed that the results of the initial test after the action in the first cycle of 30 students there were 19 students who completed (63, 33%), while in the second cycle the number of students who completed as many as 26 students (86, 67%). Thus, it can be proven that the application of the Talkhis and Taqshir methods to the Tajweed subject class VII D MTs "Al-Islam" Joresan in Tajwid Chapter 1 Hal Nun Sukun and Tanwin has a positive impact on improving student learning outcomes.